2016
DOI: 10.1016/j.nano.2015.12.362
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying cellular mechanics and adhesion in renal tubular injury using single cell force spectroscopy

Abstract: Tubulointerstitial fibrosis represents the major underlying pathology of diabetic nephropathy where loss of cell-to-cell adhesion is a critical step. To date, research has predominantly focussed on the loss of cell surface molecular binding events that include altered protein ligation. In the current study, atomic force microscopy single cell force spectroscopy (AFM-SCFS) was used to quantify changes in cellular stiffness and cell adhesion in TGF-β1 treated kidney cells of the human proximal tubule (HK2). AFM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Whilst the structural and functional disturbances discussed above are synonymous with early stages of diabetic nephropathy, tubulointerstitial fibrosis (TIF), represents the final common pathway of chronic renal failure and exhibits a positive correlation to the onset of end‐stage renal disease and entry onto the renal transplantation programme (Hodgkins & Schnaper, ). Recent findings from our laboratory confirm that tubular CX43 and CX26 expression is increased in biopsy material from people with diabetic nephropathy (Siamantouras, Hills, Squires, & Liu, ), and work by Abed et al ., reported that patients with chronic kidney disease (CKD) exhibit elevated levels of CX43. Using a mouse model of hypertension‐induced CKD, they demonstrated decreased expression of cell adhesion markers, reduced monocyte infiltration and interstitial renal fibrosis when CX43 expression was reduced by 50%.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Whilst the structural and functional disturbances discussed above are synonymous with early stages of diabetic nephropathy, tubulointerstitial fibrosis (TIF), represents the final common pathway of chronic renal failure and exhibits a positive correlation to the onset of end‐stage renal disease and entry onto the renal transplantation programme (Hodgkins & Schnaper, ). Recent findings from our laboratory confirm that tubular CX43 and CX26 expression is increased in biopsy material from people with diabetic nephropathy (Siamantouras, Hills, Squires, & Liu, ), and work by Abed et al ., reported that patients with chronic kidney disease (CKD) exhibit elevated levels of CX43. Using a mouse model of hypertension‐induced CKD, they demonstrated decreased expression of cell adhesion markers, reduced monocyte infiltration and interstitial renal fibrosis when CX43 expression was reduced by 50%.…”
Section: Introductionsupporting
confidence: 83%
“…How aberrant CX‐mediated communication impacts on cell function forms the basis of our ongoing studies. In early TIF, exposure to glucose and downstream pro‐fibrotic cytokines initiates a series of events beginning with altered expression of the epithelial adhesion protein E‐cadherin (Hills et al., ; Siamantouras et al., ). Cadherins help form the multi‐protein adherens junction that links cell‐to‐cell contact to the actin cytoskeleton and associated signalling molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human kidney (HK2) cells (passage 18-30) were maintained in DMEM/Hams F12 medium, supplemented with 10% FCS wt/vol, glutamine (2mmol/l) and EGF (5ng/ml), and cultured at 37°C in a humidified atmosphere with 5% CO 2 . Prior to treatment, cells were transferred to DMEM/F12 low glucose (5mmol/l) for 48h as described previously [26]. Cells were serum-starved overnight before incubating in TGF-β1 (2–10ng/ml), glucose (25mmol/l), conditioned media or L-glucose (25mmol/l) for 48h.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, particular molecules derived from extracellular exosomes have been suggested to serve as potential diagnostic biomarkers in DN including AQP2(22), AQP5(22) and let-7c-5p(23). The loss of molecularbinding events between cell surfaces is also involved in diabetic tubulointerstitial fibrosis(24). KEGG pathway analysis of targeted DEGs showed that these DEGs were primarily mapped to complement and coagulation cascades, tight junction and cell adhesion molecules.…”
mentioning
confidence: 99%